48 Treatment of heart failure in 2020: champs or chumps?. (30th September 2020) - Cusack, R; Radhakrishna, A; Barton, J
Abstract : Introduction: The importance of achieving target doses of guideline directed medical therapy (GDMT) for patients with heart failure with reduced ejection fraction (HFrEF) is well established. Recently, large registry studies conducted in both the United States (CHAMP-HF) and in Europe (CHECK-HF) have identified while much progress has been made compared with similar studies in the early part of the millennium, significant deficiencies in prescribing trends and adherence to guidelines still remain. Our goal was to conduct an audit of prescribing trends in a tertiary referral centre at University Hospital Galway, within a specialist-led heart failure outpatient clinic service, to evaluate our performance in comparison to these large studies. Methods: A retrospective audit was conducted on all patients with HFrEF attending the outpatient heart failure clinic at University Hospital Galway between January and March 2020. Demographic and clinical data included age, gender, ejection fraction, NYHA class, comorbidities (in particular type 2 diabetes), aetiology of cardiomyopathy, history of admissions with decompensation within 12 months, history of ICD/CRT implantation, systolic blood pressure and pulse rate. Biochemical data included estimated glomerular filtration rate, NTproBNP and potassium levels. Medication data included types and doses of GDMT, reasons (if documented) for not being on target dose, loop diuretic doses, and whether the patient was prescribed a SGLT2 inhibitor. Results: Data was collected on a total of 129 patients with a mean age of 71.3. 69% were male with a mean LVEF of 28.5%. Overall usage of RAS inhibitors and beta blockers was better than or comparable to existing large scale studies. However, a low proportion of patients on optimal dosing of these therapies was observed, consistent with existing data. A much larger proportion (45.7%) of our cohort were prescribed an ARNI than in either CHAMP-HF or CHECK-HF, likely a reflection of the approval of the drug occurring partway though the studies. Regrettably our centre performed relatively poorly in both prescription and uptitration of MRAs. In terms of reasons underlying non-prescription or suboptimal dosing, with the exception of ACEI/ARBs no clearly documented or identifiable reason made up the largest proportion of each drug group. Of note only 6 patients (4.7%) were prescribed SGLT2 inhibitors; all of these patients were diabetic. Conclusions: Despite the strong body of evidence underpinning GDMT, gaps in prescribing habits still exist with specialist heart failure outpatient services. In particular issues around more widespread use of MRAs continue to undermine optimal therapy for heart failure. The low usage of SGLT2 inhibitors despite compelling evidence from the DAPA-HF trial is likely secondary to the lack of established guidelines on its use; we would expect this to be addressed in the next update to the ESC Guidelines.